Structural insights of human mitofusin-2 into mitochondrial fusion and CMT2A onset - Yu-Jie Li (Nature Portfolio, 2019)
Mitofusin-2 (MFN2) is a dynamin-like GTPase that plays a central role in regulating mitochondrial fusion and cell metabolism. Here, authors report crystal structures of truncated human MFN2 in different nucleotide-loading states and show that MFN2 forms sustained dimers even after GTP hydrolysis.